Wall Climbing Robot Using Electrostatic Adhesion Force Generated by Flexible Interdigital Electrodes. (14th January 2013) - Liu, Rong; Chen, Rui; Shen, Hua; Zhang, Rong
Electrostatic adhesion technology has broad application prospects on wall climbing robots because of its unique characteristics compared with other types of adhesion technologies. A double tracked wall climbing robot based on electrostatic adhesion technology is presented including electrode panel design, mechanical structure design, power supply system design and control system design. A theoretical adhesion model was established and the electrostatic potential and field were expressed by series expansions in terms of solutions of the Laplace function. Based on this model, the electrostatic adhesion force was calculated using the Maxwell stress tensor formulation. Several important factors which may influence the electrostatic adhesion force were analysed and discussed by both FEM simulation and theoretical calculation. In addition, experiments on the adhesion performance of the electrode panel and the climbing performance of the robot on various wall materials were carried out. Both the simulation and experiment results verify the feasibility of electrostatic adhesion technology being applied on wall climbing robots. The theoretical model and calculation method for the electrostatic adhesion force proposed in this paper are also justified.